Vertebral Fractures: Which Radiological Criteria Are Better Associated With the Clinical Course of Osteoporosis?. Issue 1 (February 2021) - Lentle, Brian C.; Berger, Claudie; Brown, Jacques P.; Probyn, Linda; Langsetmo, Lisa; Hammond, Ian; Hu, Jeff; Leslie, William D.; Prior, Jerilynn C.; Hanley, David A.; Adachi, Jonathan D.; Josse, Robert G.; et al.
Study Purpose: Morphometric methods categorize potential osteoporotic vertebral fractures (OVF) on the basis of loss of vertebral height. A particular example is the widely used semiquantitative morphometric tool proposed by Genant (GSQ). A newer morphologic algorithm-based qualitative (mABQ) tool focuses on vertebral end-plate damage in recognizing OVF. We used data from both sexes in the Canadian Multicentre Osteoporosis Study (CaMos) to compare the 2 methods in identifying OVF at baseline and during 10 years of follow-up. Materials and Methods: We obtained lateral thoracic and lumbar spinal radiographs (T4-L4) 3 times, at 5-year intervals, in 828 participants of the population-based CaMos. Logistic regressions were used to study the association of 10-year changes in bone mineral density (BMD) with incident fractures. Results: At baseline, 161 participants had grade 1 and 32 had grade 2 GSQ OVF; over the next 10 years, only 9 of these participants had sustained incident GSQ OVF. Contrastingly, 21 participants at baseline had grade 1 and 48 grade 2 mABQ events; over the next 10 years, 79 subjects experienced incident grade 1 or grade 2 mABQ events. Thus, incident grades 1 and 2 morphologic fractures were 8 times more common than morphometric deformities alone. Each 10-year decrease of 0.01 g/cm 2 in total hip BMD was associated with a 4.1% (95% CI: 0.7-7.3) higher odds of having an incident vertebral fracture. Conclusions: This analysis further suggests that morphometric deformities and morphologic fractures constitute distinct entities; morphologic fractures conform more closely to the expected epidemiology of OVF.